2003
DOI: 10.1016/s0002-9440(10)63897-7
|View full text |Cite
|
Sign up to set email alerts
|

Kindling Status in Sprague-Dawley Rats Induced by Pentylenetetrazole

Abstract: Kindled seizures are widely used as a model for epileptogenesis. Although the achievement of kindling criterion is known to require time to develop, the precise developmental period has not been identified. We now report that optimal achievement of the kindling criterion in the Sprague-Dawley rat is associated with a critical inter-stimulus interval of 24 to 26 days. We show that highly efficient kindling can be achieved with only two subconvulsive doses of pentylenetetrazole so long as they are given 25 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 28 publications
3
33
1
Order By: Relevance
“…In accordance with previous studies, the rats in this study were extremely susceptible to the development of kindling status by PTZ subconvulsant stimulation [33]. It is known that, by competitively interacting with GABA A receptors, PTZ induces convulsion in rats - presumably by impairing the GABA-mediated neuronal inhibition [34].…”
Section: Discussionsupporting
confidence: 86%
“…In accordance with previous studies, the rats in this study were extremely susceptible to the development of kindling status by PTZ subconvulsant stimulation [33]. It is known that, by competitively interacting with GABA A receptors, PTZ induces convulsion in rats - presumably by impairing the GABA-mediated neuronal inhibition [34].…”
Section: Discussionsupporting
confidence: 86%
“…We previously reported that optimal kindling status is achieved when PTZ is administered within a tight time window of 25±1 day [1]. In the present study, we found that the number of DCX + cells also is maximal when PTZ is administered every 25 th day (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Kindling criterion was maintained by four subsequent subconvulsive doses of PTZ (30 mg/kg) given 25±1 days apart [1]. In order to evaluate cell accumulation and cellular phenotype, rats were given BrdU (50 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Cortical epileptiform activities were induced by slow injection (within 2 min) of pentylenetetrazole (PTZ, Sigma, USA) via the jugular vein at 60 mg/100 g body weight [16]. Repeated injections with the same dose of PTZ were given when the epileptiform activities were dwindling, usually 1-2 h after the previous injection.…”
Section: Epileptic Modelmentioning
confidence: 99%